PEMBERIAN UPAH PEKERJA DITINJAU DARI UPAH MINIMUM KABUPATEN DAN HUKUM EKONOMI ISLAM - Sari, Septi Wulan (IAIN Tulungagung, 2016)
Waging system becomes a complex problem between the employersand the workers whose bargaining position is always weak. To protectthe workers’ rights, the government has set up the regional minimumwage. As a matter of fact, this regulation has not been well implementedsince there are a lot of workers who are paid under the standard. Thisstudy is intended to investigate the waging system of home industriesat Tanjungsari Village. This study constitutes a case study whichemploys descriptive qualitative approach. The data are collectedthrough deep interview and field observation and documentation.The data are analyzed using descriptive qualitative method. Thisstudy reveals that (1) there are two kinds of waging system: daily andcontract, (2) the wage for the skillful workers has meet the wagingstandard, but the wage for the unskillful workers is still under thestandard, and (3) the waging system, in some cases, has not meet theIslamic waging standard in which the wage is given based on fairness,appropriateness, mutual benefit, and on time.Kata kunci: Sistem Pengupahan, Upah Minimum Kabupaten, HukumEkonomi